Transport stress affects the fecal microbiota in healthy donkeys. (31st July 2021) - Jiang, Guimiao; Zhang, Xinhao; Gao, Weiping; Ji, Chuanliang; Wang, Yantao; Feng, Peixiang; Feng, Yulong; Zhang, Zhiping; Li, Lin; Zhao, Fuwei
Abstract: Background: With the development of large‐scale donkey farming in China, long‐distance transportation has become common practice, and the incidence of intestinal diseases after transportation has increased. The intestinal microbiota is important in health and disease, and whether or not transportation disturbs the intestinal microbiota in donkeys has not been investigated. Objectives: To determine the effects of transportation on the fecal microbiota of healthy donkeys using 16S rRNA sequencing. Animals: Fecal and blood samples were collected from 12 Dezhou donkeys before and after transportation. Methods: Prospective controlled study. Cortisol, ACTH, and heat‐shock protein 90 (HSP90) concentrations were measured. Sequencing of 16S rRNA was used to assess the microbial composition. Alpha diversity and beta diversity were assessed. Results: Results showed significant ( P  < .05) increases in cortisol (58.1 ± 14.6 to 71.1 ± 9.60 ng/mL), ACTH (163.8 ± 31.9 to 315.8 ± 27.9 pg/mL), and HSP90 (10.8 ± 1.67 to 14.6 ± 1.75 ng/mL) on the day of arrival. A significantly lower ( P  = .04) level of bacterial richness was found in fecal samples after transportation, compared with that before transportation without distinct changes in diversity. Most notably, donkeys had significant decreases in Atopostipes, Eubacterium, Streptococcus, and Coriobacteriaceae . Conclusions and Clinical Importance: Transportation can induce stress in healthy donkeys and have some effect on the composition of the in fecal microbiota. Additional studies are required to understand the potential effect of these microbiota changes, especially significantly decreased bacteria, on the development intestinal diseases in donkeys during recovery from transportation.